Simple and Sensitive High Performance Liquid Chromatographic (HPLC) Method for the Determination of the Apigenin from Dried Powder of Cosmos Bipinnatus, Apium Graveolens and Petroselinum Crispum: Determination of Apigenin in dried powder of plants - Ali Sharafi,; Soroush Bijani,; Hamidreza Kheiri-Manjili,; Alireza Ahmadnia,; Hossein Danafar, (Iranian Journal of Pharmaceutical Sciences, 2016)
Apigenin is best known as an irreversible inhibitor of monoamine oxidase (MAO), an intracellular enzyme associated with the outer membrane of mitochondria. The purpose of this study is to establish a reliable and quick method for the assignment of apigenin in Cosmos bipinnatus, Apium graveolens, and Petroselinum crispum by HPLC. A rapid and sensitive HPLC method has been developed for determination of apigenin. Mobile phase was composed water-acetonitrile (55:45 v/v) with a flow rate of 1 ml/min and the eluted peaks were detected by a UV detector set at wavelength of 340 nm. The method was validated in the range of apigenin concentrations from 0.01 to 500 μg/ml and the limits of detection (LOD) and quantitation (LOQ) of the method were 0.005 and 0.01 μg/ml, respectively. The average recovery throughout the linear concentration range was 97.28 percent and the averages for within-run and between-run accuracy values were 99.32 and 96.79 respectively. The method is quick, simple, sensitive, and precise for the screen, assignment, and evaluation of apigenin in plants by HPLC.